The physical and Legal Disappearance of the Subject of the Administrative Decision - Sameh Lutfi, Ola (International Journal of Psychosocial Rehabilitation, 2020)
This research deals with the physical and legal disappearance of the subject of the administrative decision outside the judiciary way. The research is limited to the ways of disappearance of usual nature, the ways that are for reasons beyond the will, the waiver of the one who has rights according to these decisions, as well as how to complete the waiver, and the cases that enable the administration to end the decisions by an individual will, and finally the disappearance of the administrative decision because of negligence or abandonment, due to the absence of its application requirements.